Kenya Economic Update, June 2021 : Rising Above the Waves - World Bank (World Bank, Washington, DC, 2021)
The pandemic has dealt a major blow to the economy, but the government’s quick policy responses have helped to cushion the impact, and a partial recovery is underway. In response to the improving conditions, many of the tax and regulatory relief measures extended at the onset of the crisis have been discontinued. The economy is expected to continue to recover and gradually return to growth of above 5 percent. The near-term economic outlook for Kenya, as elsewhere, remains unusually uncertain and contingent on the course of the pandemic.